2021
DOI: 10.1002/jgm.3394
|View full text |Cite
|
Sign up to set email alerts
|

LINC01291 promotes hepatocellular carcinoma development by targeting the miR‐186‐5p/OXSR1 axis

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide. Recent studies have demonstrated that lncRNAs play an important role in tumorigenesis. LINC01291 has been confirmed to be involved in the proliferation and migration of different cancers, although the function of LINC01291 in HCC is still unknown.Methods: First, the expression of LINC01291 in 50 paired HCC tissues, adjacent normal tissues and HCC cell lines was measured by a quantitative real-time polymerase chain reaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…OXSR1 can combine with miR-25-3p to inhibit epileptiform discharges (31). OXSR1 contributes to hepatocellular carcinoma cell proliferation and motility by interacting with miR-186-5p as well as LINC01291 (32). Another study showed that OXSR1 expression was associated with vascular dysfunction and hypertension in autosomal-dominant polycystic kidney disease (33).…”
Section: Discussionmentioning
confidence: 99%
“…OXSR1 can combine with miR-25-3p to inhibit epileptiform discharges (31). OXSR1 contributes to hepatocellular carcinoma cell proliferation and motility by interacting with miR-186-5p as well as LINC01291 (32). Another study showed that OXSR1 expression was associated with vascular dysfunction and hypertension in autosomal-dominant polycystic kidney disease (33).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has indicated that the abnormal expression of miR-186-5p might partake in the regulation of malignant behaviors in different human cancers. 35,36 Of interest, related literature suggested that miR-186 might serve as a carcinogenic factor by promoting cell growth in CSCC. 20,37 In accordance with these previous studies, our data exhibited that miR-186-5p could be highly expressed in tumor tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…The RIP experiment was further verified, and it was found that miR‐186‐5p could bind with hsa_circ_0005085 in a targeted manner. Recent research has indicated that the abnormal expression of miR‐186‐5p might partake in the regulation of malignant behaviors in different human cancers 35,36 . Of interest, related literature suggested that miR‐186 might serve as a carcinogenic factor by promoting cell growth in CSCC 20,37 .…”
Section: Discussionmentioning
confidence: 99%